Cutting balloons, covered stents and paclitaxel-coated balloons for the treatment of dysfunctional dialysis access. (1st December 2016) - Kitrou, Panagiotis; Spiliopoulos, Stavros; Karnabatidis, Dimitris; Katsanos, Konstantinos
ABSTRACT: Introduction : Percutaneous transcatheter balloon angioplasty has evolved to the current mainstay treatment for salvage of dysfunctional dialysis access. Nonetheless, it is frequently associated with recurrent vessel restenosis and the need for multiple repeat treatments in order to maintain hemodynamic patency. Cutting-balloons, covered stents or stent-grafts, and paclitaxel-coated balloons have been extensively tested and investigated with the aim to improve immediate anatomical and long-term clinical results. Areas covered : In the present overview, we discuss the background and appraise relevant medical literature on the aforementioned technologies and provide a more in-depth synthesis of the results of different clinical studies for each device category. We will also discuss the limitations in the mode of action of each group of devices and envision what the future holds for the challenging field of dialysis access interventions. Expert commentary : We propose a good practice algorithm for the treatment of thrombosed or dysfunctional dialysis access.